Education as a pedagogic category in context of globalization and call of the time (Pedagogy of Higher and Secondary Education, 2014)
Kovshar O. V. Education as a pedagogic category in context of globalization and call of the timeThe author explains the phenomenon of education from the standpoint of which one can best contribute to socialization of people, his or her optimal adaptation to social life. The author also determines the importance of globalization and modernization of modern education. The article focuses on the principlesб functions and approaches of its organization.
Keywords: education; education as a process; globalization of education; features of modern education; principles of education; self-organization; interaction